2015
DOI: 10.3390/lubricants3030539
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analyses of the Toxicity, Immunological, and Gene Expression Effects of Cobalt-Chromium Alloy Wear Debris and Co Ions Derived from Metal-on-Metal Hip Implants

Abstract: Joint replacement has proven to be an extremely successful and cost-effective means of relieving arthritic pain and improving quality of life for recipients. Wear debris-induced osteolysis is, however, a major limitation and causes orthopaedic implant aseptic loosening, and various cell types including macrophages, monocytes, osteoblasts, and osteoclasts, are involved. During the last few years, there has been increasing concern about metal-on-metal (MoM) hip replacements regarding adverse reactions to metal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 177 publications
(195 reference statements)
0
17
0
Order By: Relevance
“…The production of CoCr alloy wear debris leads to phagocytosis of the particles by macrophages [28] . This metal debris with associated ions activate the monocyte/macrophage lineage to release a variety of mediators, such as free radicals, nitric oxide, tumour necrosis factor-α (TNF-α), interleukin-1 β (IL-1 β), prostaglandin E2 (PGE2) and IL-6 [29] , [30] , [31] , [32] , which are influenced by the concentrations, shape and size of the particles [4] . Metal debris and ions can sensitize the immune system by inducing a delayed type IV hypersensitivity response [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The production of CoCr alloy wear debris leads to phagocytosis of the particles by macrophages [28] . This metal debris with associated ions activate the monocyte/macrophage lineage to release a variety of mediators, such as free radicals, nitric oxide, tumour necrosis factor-α (TNF-α), interleukin-1 β (IL-1 β), prostaglandin E2 (PGE2) and IL-6 [29] , [30] , [31] , [32] , which are influenced by the concentrations, shape and size of the particles [4] . Metal debris and ions can sensitize the immune system by inducing a delayed type IV hypersensitivity response [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding that, the presence of protein may also present unfavorable consequences. In another study done by Yan et al [ 56 ], it was observed that the presence of protein could undeniably accelerate the formation of ions, such implants when used in vivo would have cytotoxic effects on the neighboring cells [ 74 , 75 ].…”
Section: Tribocorrosive Behavior Of Cocrmo Alloysmentioning
confidence: 99%
“…The metallic CoCrMo is either just a part of the articulating joint, like the ball in a hip joint or the femur in a knee joint, or both articulating partners are made of metallic CoCrMo. Although artificial joint implants are produced on a high quality level already, some problems can arise from metallic ions or wear particles [2]. Blood cobalt and chromium levels of greater than 7 ppb (7 µg/L), point to potential for undesired soft tissue reaction [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although artificial joint implants are produced on a high quality level already, some problems can arise from metallic ions or wear particles [2]. Blood cobalt and chromium levels of greater than 7 ppb (7 µg/L), point to potential for undesired soft tissue reaction [2]. Even if, the articulating part in the artificial joint is a softer polymer, like UHMWPE (ultra-high molecular weight polyethylene), the metallic counterpart suffers from wear.…”
Section: Introductionmentioning
confidence: 99%